Akuntabilitas Tata Kelola Keuangan Berbasis Kearifan Lokal pada Tradisi Tari Alusu Warisan Budaya Bugis Bone - Wahyu Ardiman; Efa Fadillah; Muhammad Yamin; Imma Imma; Nurhikmah Nurhikmah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Alusu Dance is a cultural heritage of the Bugis Bone community that functions not only as a ceremonial welcoming dance but also as a representation of local cultural values and social practices. This study aims to explore the cultural values embedded in Alusu Dance and analyze its financial governance traditions as a form of cultural accounting. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, documentation, and literature studies, then analyzed through data reduction, data presentation, and conclusion drawing with source triangulation. The findings reveal that Alusu Dance reflects values of sipakatau, sipakalebbi, sipakainge’, courtesy, responsibility, solidarity, and cultural preservation. These values are manifested through dance movements, costumes, performance arrangements, and community interactions during cultural events. Financial governance practices are implemented through budgeting, fund allocation, simple financial recording, and accountability based on trust, transparency, and responsibility. These findings demonstrate that local wisdom-based financial governance contributes to sustaining Bugis Bone’s cultural heritage.